(untitled) (Applied Biological Research, 2016)
A study was undertaken to assess the efficacy of nisin on oxidative stability and microbial quality of chevon nuggets supplemented with almond and walnut at 5 and 10% level, respectively. Chevon nuggets ere aerobically packaged in low density polyethylene (LDPE) pouches along with control and evaluated for storage quality for 21 days under refrigerated conditions (4±1oC). The products were analyzed for various physico-chemical, microbial and sensory parameters. The study revealed that with increase in storage period the free fatty acid (FFA) content, thiobarbituric acid reactive substances (TBARS), total plate count and psychrophillic count showed significant increase; whereas sensory parameters showed significant decrease. Nisin treated preparations had significantly low TBARS and FFA values than non-nisin treated preparations. Nisin-treated preparations had significantly low total plate- and psychrotropic-counts. The nisin treated products were successfully stored for 14 days under refrigeratedconditions (4±1oC) in LDPE pouches and the product showed better acceptability.